Analisis Fenomena Authority Trap dalam Kewenangan Pemerintah Daerah dalam Menjalankan SDGS 7 Affordable and Clean Energy - M. Haidar Hafizh Daniar; Muhammad Fathoni Ridzakiy; Naomira Gadieza Putri; Iyep Saefulrahman (Pusat Riset dan Inovasi Nasional, 2026)
The phenomenon of authority trap occurs when local governments are burdened with achieving SDG 7 (“Affordable and Clean Energy”) targets without being granted adequate authority and resources. This study examines the context of West Java Province and Bandung City, which face complex clean energy governance due to fragmented authority across levels of government. At the national level, Government Regulation No. 40/2025 reinforces emission reduction and the transition toward Net-Zero Emissions by 2060. West Java has established RUED No. 2/2019, which sets a minimum renewable energy share of 17% by 2025. However, the technical responsibilities for implementation (such as electrification and energy conservation) lie at the regency/municipal level. The analysis highlights fiscal disparities, PLN’s dominance, and national regulations that override local authority. Local innovations such as rooftop solar PV, solar-powered street lighting, the Green Building Mayor Regulation, and PPP schemes are evaluated for their effectiveness. This qualitative study combines policy document analysis and literature review. The findings show that the absence of strong local regulation (regulatory void) and the central dominance of PLN reinforce the authority trap, hindering synergy among stakeholders. The recommendations emphasize strengthening institutional collaboration, aligning local and national regulatory frameworks, and promoting innovative financing mechanisms to enable Bandung City to break free from the authority trap in achieving SDG 7 targets.